Conductive adhesive for carbon coating of current collector and preparation method of conductive adhesive

Through the synergistic effect of hybrid polyacrylic acid and modified filler in conductive adhesives, the problem of insufficient bonding capacity and conductivity of existing conductive adhesives is solved, and significantly improved adhesive strength, conductivity and Thermal conductivity.

CN119391336AInactive Publication Date: 2025-02-07ANHUI NANDU HUATUO NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411530858.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The adhesive capacity and electrical conductivity of existing conductive adhesives need to be further improved, especially in terms of the adhesive force of metal current collectors and the conductivity of materials.

Method used

Using hybrid polyacrylic acid as the main body, combining the synergistic effect of silane coupling agent and carbonate crosslinker, high concentration of cyano groups and epoxy groups were introduced to prepare a conductive adhesive for current collector coating, and through Nanosilver particles are embedded on the graphene surface to prepare modified fillers to improve their electrical and thermal conductivity.

Benefits of technology

It significantly improves the polarity of the conductive adhesive, enhances the adhesive force with the metal current collector, improves the shear strength, wear resistance and thermal conductivity of the material, and optimizes the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391336A_ABST
    Figure CN119391336A_ABST
Patent Text Reader

Abstract

The invention discloses a conductive adhesive for carbon coating of a current collector and a preparation method of the conductive adhesive. The conductive adhesive is used for solving the technical problem that in the prior art, the bonding capacity and the conductivity of a conductive adhesive need to be further improved. The water-based adhesive is prepared from 10 to 12 parts of hybrid polyacrylic acid, 12 to 16 parts of modified filler, 3 to 5 parts of butadiene styrene rubber, 2 to 3 parts of polyvinylpyrrolidone, 2 to 3 parts of polyvinylpyrrolidone, 1 to 2 parts of sodium dodecyl benzene sulfonate and 60 to 80 parts of deionized water. According to the present invention, the graphene is introduced to improve the compatibility with the inorganic material and the carbon-based material, the cyano group is introduced to enhance the polarity of the adhesive, the adhesion with the metal current collector is further improved, the nano-silver particles are embedded on the surface of the graphene to prepare the modified filler, and the nano-silver particles cooperate with the hybrid polyacrylic acid so as to significantly enhance the electrical conductivity and the thermal conductivity of the adhesive;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesive processing, and in particular to a conductive adhesive for carbon coating of a current collector and a preparation method thereof. Background Art

[0002] The development of conductive adhesives began in the 1960s. It was originally intended to replace high-temperature welding technology. With the advancement of the electronics industry, it has been continuously improved in terms of conductivity, heat resistance and mechanical adhesion. Since the 1980s, with the introduction of nanotechnology and new materials, conductivity and bonding properties have been significantly improved, and application scenarios have also expanded to flexible circuit boards, displays, and automotive electronics. After the 21st century, technologies such as nanosilver and carbon-based fillers have further optimized conductive adhesives, significantly improving the bonding ability and conductivity of conductive adhesives.

[0003] Prior art CN111918946A discloses a conductive adhesive composition, and a conductive adhesive composition, comprising a conductive filler (A) comprising silver powder (a1) and silver-coated copper powder (a2), and an adhesive composition (B), wherein the conductive adhesive composition contains 3-65wt% of silver-coated copper powder (a2) relative to the total amount of the conductive filler (A), and contains 95-99.95wt% of the conductive filler (A) relative to the total amount of non-volatile components in the conductive adhesive composition.

[0004] However, the above patent content is to add silver powder and silver-coated copper powder as conductive fillers into the conductive adhesive to achieve the purpose of improving the conductivity of the material. However, the silver component without surface modification or loading has high surface energy and lacks polar functional groups, while the surface energy of the organic component is low. This difference in properties will cause the silver component to agglomerate, making its dispersion poor, and the conductive performance of the material needs to be further improved. When the conductivity of the material varies with the change of position, the adhesive will be locally overheated, causing the material to age and reduce the bonding ability of the conductive adhesive.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide a conductive adhesive for carbon coating of a current collector and a preparation method thereof, so as to solve the technical problem that the bonding ability and conductive performance of the conductive adhesive in the prior art need to be further improved.

[0007] The object of the present invention can be achieved by the following technical scheme: a conductive adhesive for carbon coating of a current collector, comprising the following raw materials by weight: 10-12 parts of hybrid polyacrylic acid, 12-16 parts of modified filler, 3-5 parts of styrene-butadiene rubber, 2-3 parts of polyvinyl pyrrolidone, 2-3 parts of polyvinyl pyrrolidone, 1-2 parts of sodium dodecylbenzene sulfonate and 60-80 parts of deionized water;

[0008] Wherein, the preparation method of hybrid polyacrylic acid comprises the following steps:

[0009] A1, adding modified polyacrylic acid, modified crosslinking agent and N,N-dimethylformamide into a reaction kettle and stirring, raising the temperature of the reaction kettle to 60-80° C., keeping the temperature and stirring for 8-10 hours, and post-treating to obtain crosslinked polyacrylic acid;

[0010] The reaction equation for preparing cross-linked polyacrylic acid is:

[0011]

[0012] Where: R4:

[0013] The reaction principle for preparing cross-linked polyacrylic acid is as follows: Reaction principle: The carboxyl oxygen in the modified polyacrylic acid first initiates a nucleophilic attack on the carbon atom of the isocyanate group in the modified cross-linker. At this time, part of the positive charge of the carbon atom is attracted by the negative charge of the carboxyl oxygen, resulting in the breaking of the carbon-nitrogen double bond in the isocyanate group, and the carbon atom forms a new chemical bond with the attacked oxygen atom. As the double bond breaks, the nitrogen atom gains a pair of lone pairs of electrons and becomes a free amino group. After the double bond breaks, the lone pair of electrons of the nitrogen atom forms a new chemical bond with the oxygen atom next to the new carbon-oxygen bond formed by the original carboxyl oxygen, thereby generating an amide ester structure.

[0014] A2. Add cross-linked polyacrylic acid, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, triethylamine and N,N-dimethylformamide into a reaction kettle and stir. The temperature of the reaction kettle is increased to 30-50° C. and stirred for 1-2 hours. Post-treatment is performed to obtain hybrid polyacrylic acid.

[0015] The reaction equation for preparing hybrid polyacrylic acid is:

[0016]

[0017] Where: R5:

[0018] The reaction principle for preparing hybrid polyacrylic acid is as follows: under alkaline conditions, the epoxy group undergoes ring opening to generate free radicals, which react with the secondary amino group to finally prepare the hybrid polyacrylic acid.

[0019] Further, in step A1, the stirring rate of the reactor is 80-120rpm, the amount ratio of modified polyacrylic acid, modified crosslinking agent and N,N-dimethylformamide is 8-10g:2-3g:30-40mL, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is placed in a rotary evaporator at a temperature of 80-100°C, and the reaction mixture is distilled under reduced pressure until no liquid is produced to obtain cross-linked polyacrylic acid; in step A2, the amount ratio of cross-linked polyacrylic acid, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, triethylamine and N,N-dimethylformamide is 8-10g:2-3g:0.5-0.8g:40-60mL, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is placed in a rotary evaporator at a temperature of 80-100°C, and the reaction mixture is distilled under reduced pressure until no liquid is produced to obtain hybrid polyacrylic acid.

[0020] Further, the preparation method of modified polypropylene comprises the following steps:

[0021] B1. Add 1,4-dichloro-2-butene, sodium cyanide and dimethyl sulfoxide into a reaction kettle and stir. The temperature of the reaction kettle is increased to 100-120° C. and stirred for 4-6 hours. Post-process to obtain a modified monomer.

[0022] The reaction equation for preparing the modified monomer is:

[0023]

[0024] The reaction principle for preparing the modified monomer is as follows: the reaction principle of the reaction is carried out through the SN2 nucleophilic substitution mechanism. The cyanide ion generated by the dissociation of sodium cyanide acts as a nucleophilic reagent, successively attacking the halogenated carbon atoms of 1,4-dichloro-2-butene, and gradually replacing the two chlorine atoms thereon, thereby generating a modified monomer. The mass spectrometry analysis data of the modified monomer are m / z: 78.02 (100.0%), 79.03 (4.3%).

[0025] B2. Add modified monomer, acrylic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, azobisisobutylcyanide and dimethyl sulfoxide into a reactor, increase the temperature of the reactor to 80-100°C, keep the reaction warm for 2-4 hours, and obtain modified polyacrylic acid by post-treatment.

[0026] The reaction equation for preparing modified polyacrylic acid is:

[0027]

[0028] Where: R1:

[0029] The reaction principle for preparing modified polyacrylic acid is as follows: under high temperature and the catalysis of a free radical initiator, a free radical polymerization reaction occurs between monomers, and modified polyacrylic acid is finally obtained through continuous polymerization between monomers.

[0030] Further, in step B1, the stirring rate of the reactor is 80-120rpm, the amount ratio of 4-dichloro-2-butene, sodium cyanide and dimethyl sulfoxide is 4-5mL:4-5g:10-15mL, and the post-treatment includes: after the reaction is completed, the reactor is lowered to room temperature, the temperature of the reactor is lowered to 5°C and the reaction liquid is filtered, the filtrate is collected, and the filtrate is placed in a rotary evaporator at a temperature of 80-100°C, and the filtrate is distilled under reduced pressure until no liquid is produced to obtain a modified monomer; in step B2, the modified monomer, propylene The dosage ratio of olefinic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, azobisisobutylcyanide and dimethyl sulfoxide is 3-5g:6-8g:9-12g:0.3-0.5g:60-80mL. The post-treatment includes: after the reaction is completed, the reaction kettle is lowered to room temperature, the reaction liquid is placed in a rotary evaporator at a temperature of 80-100°C, and the reduced pressure distillation is carried out until no liquid is produced to obtain modified polyacrylic acid.

[0031] Furthermore, the preparation method of the modified crosslinking agent comprises the following steps:

[0032] C1, adding 1,3-diamino-2-hydroxypropane, dimethyl carbonate, triethylamine and dimethyl sulfoxide into a reaction kettle and stirring, raising the temperature of the reaction kettle to 60-80° C., keeping the temperature for reaction for 2-4 hours, and post-treating to obtain a carbonated cross-linking agent;

[0033] The reaction equation for preparing the carbonation cross-linking agent is:

[0034]

[0035] Where: R2:

[0036] The reaction principle for preparing the carbonated cross-linking agent is as follows: under high temperature and the catalysis of an alkaline catalyst, 1,3-diamino-2-hydroxypropane and dimethyl carbonate undergo an ester exchange reaction to form a methoxycarbonyl intermediate, which is then attacked by a hydroxyl group in another 1,3-diamino-2-hydroxypropane molecule to form a structure cross-linked by a carbonate bond, thereby finally preparing the carbonated cross-linking agent. The mass spectrometry analysis data of the carbonated cross-linking agent are m / z: 206.14 (100.0%), 207.14 (7.9%), 207.13 (1.5%), and 208.14 (1.0%).

[0037] C2. Add the carbonated crosslinking agent, triethylamine and dichloromethane into the reactor, lower the temperature of the reactor by 0-5°C, add methyl chloroformate into the reactor, keep the temperature for 2-4 hours, raise the temperature of the reactor to 100-150°C, keep the temperature for 4-6 hours, and obtain the modified crosslinking agent by post-treatment.

[0038] The reaction equation for preparing the modified crosslinking agent is:

[0039]

[0040] Where: R3:

[0041] The reaction principle for preparing the modified cross-linking agent is as follows: in the reaction, the nitrogen atom of the carbonated cross-linking agent is rich in lone pair electrons and therefore exhibits strong nucleophilicity, which attacks the carbonyl carbon in the chloroformate. Since the carbonyl carbon has a partial positive charge due to the electron-withdrawing effect of oxygen, it is susceptible to nucleophilic attack, resulting in redistribution of the electron density of the carbonyl carbon, causing the chloride ion to leave the chloroformate to form a carbamate. During further heating, the bond between the carbonyl and amino groups of the carbamate is broken to form an isocyanate group, and finally a modified cross-linking agent is prepared. The mass spectrometry data of the modified cross-linking agent are m / z: 310.05 (100.0%), 311.06 (12.3%), 312.06 (2.3%), and 311.05 (1.5%).

[0042] Further, in step C1, the stirring rate of the reactor is 80-120rpm, the amount ratio of 1,3-diamino-2-hydroxypropane, dimethyl carbonate, triethylamine and dimethyl sulfoxide is 5-8g:2-3g:0.5-0.8g:20-30mL, the stirring rate of the reactor is 80-120rpm, and the post-treatment includes: after the reaction is completed, the reactor is lowered to room temperature, the reaction liquid is placed in a rotary evaporator at a temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain a carbonated cross-linking agent; in step C2, the amount ratio of the carbonated cross-linking agent, triethylamine, dichloromethane and methyl chloroformate is 3-5g:0.5-0.8g:40-60mL:10-12g, and the post-treatment includes: after the reaction is completed, the reactor is lowered to room temperature, the reaction liquid is placed in a rotary evaporator at a temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain a modified cross-linking agent.

[0043] Furthermore, the preparation method of the modified filler comprises the following steps:

[0044] D1. Add the metal alcohol solution dropwise into a reactor containing the graphene dispersion and stir, and perform ultrasonic stirring at room temperature. After the metal alcohol solution is added dropwise, continue stirring and ultrasonic stirring for 10-15 minutes to obtain a reaction solution;

[0045] D2, adding the hydrolyzate dropwise into the reaction kettle containing the reaction solution and stirring, raising the temperature of the reaction kettle to 50-60°C, controlling the pH of the reaction system to 8-9 while adding the hydrolyzate dropwise, keeping the temperature and stirring for 1-2 hours, and letting it stand for 3-5 hours to obtain a modified gel;

[0046] D3. Place the modified gel in a vacuum drying oven, raise the temperature of the vacuum drying oven to 80°C, and after vacuum drying for 10-12 hours, transfer the material to a tubular furnace, introduce nitrogen protection, and heat the tubular furnace to 350-400°C at a heating rate of 5°C / min, and keep the temperature for 2-3 hours to obtain a modified filler.

[0047] Furthermore, in step D1, the stirring rate of the reactor is 80-120rpm, the ultrasonic frequency is 20-40kHz, the metal alcohol solution is prepared by silver nitrate and ethanol in a dosage ratio of 1-2g:50mL, the graphene dispersion is prepared by graphene and ethanol in a dosage ratio of 0.2-0.5g:50mL, and the dosage ratio of the metal alcohol solution to the graphene dispersion is 1mL:1-1.5mL; in step D2, the hydrolyzate is a 25-30wt% ammonia solution.

[0048] The present invention also provides a method for preparing a conductive adhesive for current collector carbon coating: hybrid polyacrylic acid, modified filler, styrene-butadiene rubber, polyvinyl pyrrolidone, polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate and deionized water are added into a reaction kettle and stirred to obtain a conductive adhesive.

[0049] The present invention has the following beneficial effects:

[0050] 1. The conductive adhesive prepared by the present invention is mainly based on hybrid polyacrylic acid, combined with the synergistic effect of silane coupling agent and carbonate crosslinker, effectively improving its compatibility with inorganic materials and carbon-based modified fillers, especially the introduction of high-concentration cyanide groups significantly enhances the polarity of the adhesive, and greatly improves the adhesion with the metal current collector. In addition, the presence of epoxy groups not only helps the formation of SEI film as an electrolyte film-forming additive, but also further improves the shear strength and wear resistance of the material. At the same time, the carbonate component releases carbon dioxide during the combustion process, giving the material good flame retardant properties, and the modified filler prepared by embedding nanosilver particles on the surface of graphene is coordinated with hybrid polyacrylic acid to significantly enhance the electrical conductivity and thermal conductivity of the adhesive. The high electrical conductivity and thermal conductivity of nanosilver and graphene promote each other with the excellent compatibility of the adhesive system, not only greatly improving the overall bonding performance, but also showing a strong synergistic effect in electrochemical and thermal management performance, significantly optimizing the comprehensive performance of the material.

[0051] 2. In the process of preparing hybrid polyacrylic acid, the present invention first modifies the polymer monomer, introduces a cyanide body which enhances the polarity of the organic material, and significantly improves the adhesion between the organic material and the metal current collector. In addition, by introducing an epoxy group into the modified acrylic acid, the epoxy group acts as an electrolyte film-forming additive under the action of electric current, thereby promoting the formation of the SEI film. A modified cross-linking agent with carbonate as the core is obtained by ester exchange, formate formation and pyrolysis of 1,3-diamino-2-hydroxypropane. The carbonate component improves its compatibility with the carbon component in the carbonization of the current collector, significantly improves the shear strength of the material, and releases carbon dioxide during the combustion process. The organic segments of the hybrid material are cross-linked by the modified cross-linking agent, and finally cross-linked by a silane coupling agent to obtain a hybrid polyacrylic acid.

[0052] 3. In the process of preparing the modified filler, the present invention disperses the silver nitrate alcohol solution in the graphene dispersion and hydrolyzes it, and the generated gel is calcined to obtain the graphene with nano silver particles embedded on the surface, which significantly improves the conductivity of the graphene material. At the same time, as a modified filler, it has excellent compatibility with the hybrid polyacrylic acid with a carbonate group, so that it has excellent dispersibility in the adhesive, and is similar to the carbon component in the carbon coating of the current collector, so that its properties are more stable. The two cooperate with each other, so that the thermal conductivity of the material is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0054] Figure 1 The SEM images of the present invention and carbon coated on the current collector surface in different usage conditions;

[0055] In the figure: a and c are the surface SEM images of the current collector after carbonization; b is the surface SEM image of the current collector after carbonization after 250 cycles of discharge; d is the surface SEM image of the current collector after carbonization after 5 cycles of discharge. DETAILED DESCRIPTION

[0056] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0057] Example 1

[0058] This embodiment provides a conductive adhesive for carbon coating of a current collector and a preparation method thereof, comprising the following steps:

[0059] S1. Preparation of modified polyacrylic acid

[0060] Weigh: 9.0 mL of 1,4-dichloro-2-butene, 10.0 g of sodium cyanide and 24.0 mL of dimethyl sulfoxide, add them into a reactor and stir, raise the temperature of the reactor to 100° C., stir at a rate of 80 rpm, and keep stirring for 4 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, lower the temperature of the reactor to 5° C., filter the reaction liquid, collect the filtrate, place the filtrate in a rotary evaporator at a temperature of 80° C., and distill under reduced pressure until no liquid is produced to obtain a modified monomer;

[0061] Weigh: 10.0 g of modified monomer, 12.0 g of acrylic acid, 20.0 g of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 0.8 g of azobisisobutyl cyanide and 120.0 mL of dimethyl sulfoxide and add them into a reactor, the temperature of the reactor is raised to 80° C., and the reaction is kept warm for 2 hours. After the reaction is completed, the reactor is lowered to room temperature, the reaction liquid is placed in a rotary evaporator at a temperature of 80° C., and reduced pressure distillation is performed until no liquid is produced to obtain modified polyacrylic acid.

[0062] S2. Preparation of hybrid polyacrylic acid

[0063] Weigh: 12.0 g 1,3-diamino-2-hydroxypropane, 6.0 g dimethyl carbonate, 1.2 g triethylamine and 50.0 mL dimethyl sulfoxide, add them into a reactor and stir, raise the temperature of the reactor to 60° C., stir at 90 rpm, and keep warm for 2 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, place the reaction solution in a rotary evaporator at 80° C., and distill under reduced pressure until no liquid is produced to obtain a carbonated cross-linking agent;

[0064] Weigh: 8.0g of carbonated crosslinking agent, 1.2g of triethylamine and 100.0mL of dichloromethane are added to a reactor, the temperature of the reactor is lowered to 0°C, 20.0g of methyl chloroformate is added to the reactor, and the reaction is carried out for 2h at room temperature, and then the temperature of the reactor is raised to 100°C and the reaction is carried out for 4h at room temperature. After the reaction is completed, the reactor is lowered to room temperature, and the reaction liquid is placed in a rotary evaporator at a temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain a modified crosslinking agent;

[0065] Weigh: 18.0g of polyacrylic acid, 6.0g of modified crosslinking agent and 60.0mL of N,N-dimethylformamide, add them into a reactor and stir, raise the temperature of the reactor to 60°C, stir at 80rpm, keep warm and stir for 8h, after the reaction is completed, lower the temperature of the reactor to room temperature, place the reaction liquid in a rotary evaporator at 80°C, and distill under reduced pressure until no liquid is produced to obtain crosslinked polyacrylic acid;

[0066] Weigh: 18.0 g of cross-linked polyacrylic acid, 6.0 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 1.6 g of triethylamine and 100.0 mL of N,N-dimethylformamide, add into a reactor and stir, raise the temperature of the reactor to 30°C, keep warm and stir for 1 hour, after the reaction is completed, lower the temperature of the reactor to room temperature, place the reaction liquid in a rotary evaporator at a temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain hybrid polyacrylic acid.

[0067] S3. Preparation of modified filler

[0068] Weigh: 1.2 g of silver nitrate and 50.0 mL of ethanol to obtain a metal alcohol solution;

[0069] Weigh: 0.3 g of graphene and 50.0 mL of ethanol to prepare a graphene dispersion;

[0070] The metal alcohol solution is added dropwise to a reaction kettle containing a graphene dispersion solution and stirred. Ultrasound is performed while stirring at room temperature. The stirring rate is 80 rpm and the ultrasonic frequency is 20 kHz. After the metal alcohol solution is added dropwise, the stirring and ultrasonication are continued for 10 minutes to obtain a reaction solution.

[0071] A 25 wt% ammonia solution was added dropwise to a reaction kettle containing the reaction solution and stirred. The temperature of the reaction kettle was raised to 50°C. The pH of the reaction system was controlled to be 8 while the hydrolyzate was added dropwise. After stirring for 1 hour, the mixture was allowed to stand for 3 hours to obtain a modified gel.

[0072] The modified gel was placed in a vacuum drying oven, the temperature of the vacuum drying oven was increased to 80°C, and after vacuum drying for 10 hours, the material was transferred to a tubular furnace, nitrogen was introduced for protection, and the tubular furnace was heated to 350°C at a heating rate of 5°C / min, and the temperature was kept for 2 hours to obtain a modified filler.

[0073] S4. Preparation of conductive adhesive

[0074] Weigh: 10.0 g of hybrid polyacrylic acid, 12.0 g of modified filler, 3.0 g of styrene-butadiene rubber, 2.0 g of polyvinyl pyrrolidone, 2.0 g of polyvinyl pyrrolidone, 1.0 g of sodium dodecylbenzene sulfonate and 60.0 g of deionized water, add into a reaction kettle and stir to obtain a conductive adhesive.

[0075] Example 2

[0076] This embodiment provides a conductive adhesive for carbon coating of a current collector and a preparation method thereof, comprising the following steps:

[0077] S1. Preparation of modified polyacrylic acid

[0078] Weigh: 10.0 mL 1,4-dichloro-2-butene, 8.0 g sodium cyanide and 24.0 mL dimethyl sulfoxide are added to a reactor and stirred. The temperature of the reactor is raised to 120° C., the stirring rate is 120 rpm, and the mixture is stirred for 6 hours at this temperature. After the reaction is completed, the reactor is lowered to room temperature, the temperature of the reactor is lowered to 5° C., the reaction liquid is filtered, and the filtrate is collected. The filtrate is placed in a rotary evaporator at a temperature of 100° C. and distilled under reduced pressure until no liquid is produced to obtain a modified monomer;

[0079] Weigh: 8.0 g of modified monomer, 12.0 g of acrylic acid, 20.0 g of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 0.8 g of azobisisobutyl cyanide and 120.0 mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 100° C., and keep the reaction for 4 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, place the reaction solution in a rotary evaporator at a temperature of 100° C., and distill under reduced pressure until no liquid is produced to obtain modified polyacrylic acid.

[0080] S2. Preparation of hybrid polyacrylic acid

[0081] Weigh: 12.0 g 1,3-diamino-2-hydroxypropane, 6.0 g dimethyl carbonate, 1.6 g triethylamine and 50.0 mL dimethyl sulfoxide, add into the reaction kettle and stir, raise the temperature of the reaction kettle to 80° C., stir at 120 rpm, keep warm for 4 hours, after the reaction is completed, lower the temperature of the reaction kettle to room temperature, place the reaction liquid in a rotary evaporator at 100° C., and distill under reduced pressure until no liquid is produced, to obtain a carbonated cross-linking agent;

[0082] Weigh: 8.0g of carbonated crosslinking agent, 1.6g of triethylamine and 100.0mL of dichloromethane are added to a reactor, the temperature of the reactor is lowered by 5°C, 24.0g of methyl chloroformate is added to the reactor, and the reaction is carried out for 4h, the temperature of the reactor is increased to 150°C, and the reaction is carried out for 6h. After the reaction is completed, the reactor is lowered to room temperature, the reaction liquid is placed in a rotary evaporator at a temperature of 100°C, and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain a modified crosslinking agent;

[0083] Weigh: 18.0 g of polyacrylic acid, 6.0 g of modified crosslinking agent and 70.0 mL of N,N-dimethylformamide, add them into a reactor and stir, raise the temperature of the reactor to 80° C., stir at a rate of 120 rpm, and keep stirring for 10 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, place the reaction solution in a rotary evaporator at a temperature of 100° C., and distill under reduced pressure until no liquid is produced to obtain crosslinked polyacrylic acid;

[0084] Weigh: 20.0 g of cross-linked polyacrylic acid, 6.0 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 1.6 g of triethylamine and 100.0 mL of N,N-dimethylformamide, add into a reactor and stir, raise the temperature of the reactor to 50°C, keep warm and stir for 2 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, place the reaction liquid in a rotary evaporator at a temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain hybrid polyacrylic acid.

[0085] S3. Preparation of modified filler

[0086] Weigh: 1.6 g of silver nitrate and 50.0 mL of ethanol to obtain a metal alcohol solution;

[0087] Weigh: 0.4 g of graphene and 50.0 mL of ethanol to prepare a graphene dispersion;

[0088] The metal alcohol solution was added dropwise to a reaction kettle containing a graphene dispersion solution and stirred, and ultrasonication was performed while stirring at room temperature, with a stirring rate of 120 rpm and an ultrasonic frequency of 40 kHz. After the metal alcohol solution was added dropwise, the stirring and ultrasonication were continued for 15 minutes to obtain a reaction solution;

[0089] A 30 wt % ammonia solution was added dropwise to a reaction kettle containing the reaction solution and stirred. The temperature of the reaction kettle was raised to 60° C. The pH of the reaction system was controlled to be 9 while the hydrolyzate was added dropwise. The mixture was stirred for 2 h and then allowed to stand for 5 h to obtain a modified gel.

[0090] The modified gel was placed in a vacuum drying oven, the temperature of the vacuum drying oven was increased to 80°C, and after vacuum drying for 12 hours, the material was transferred to a tubular furnace, nitrogen was introduced for protection, and the tubular furnace was heated to 400°C at a heating rate of 5°C / min, and the temperature was kept for 2-3 hours to obtain a modified filler.

[0091] S4. Preparation of conductive adhesive

[0092] Weigh: 12.0 g of hybrid polyacrylic acid, 16.0 g of modified filler, 5.0 g of styrene-butadiene rubber, 3.0 g of polyvinyl pyrrolidone, 3.0 g of polyvinyl pyrrolidone, 2.0 g of sodium dodecylbenzene sulfonate and 72.0 g of deionized water, add into a reaction kettle and stir to obtain a conductive adhesive.

[0093] Example 3

[0094] This embodiment provides a conductive adhesive for carbon coating of a current collector and a preparation method thereof, comprising the following steps:

[0095] S1. Preparation of modified polyacrylic acid

[0096] Weigh: 10.0 mL 1,4-dichloro-2-butene, 10.0 g sodium cyanide and 12.0 mL dimethyl sulfoxide, add to the reactor and stir, raise the temperature of the reactor to 110° C., stir at a rate of 100 rpm, and stir for 5 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, lower the temperature of the reactor to 5° C., filter the reaction liquid, collect the filtrate, place the filtrate in a rotary evaporator at a temperature of 90° C., and distill under reduced pressure until no liquid is produced to obtain a modified monomer;

[0097] Weigh: 8.0 g of modified monomer, 12.0 g of acrylic acid, 20.0 g of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1.0 g of azobisisobutyl cyanide and 120.0 mL of dimethyl sulfoxide and add them into a reactor, the temperature of the reactor is raised to 90° C., and the reaction is kept warm for 3 hours. After the reaction is completed, the reactor is lowered to room temperature, the reaction liquid is placed in a rotary evaporator at a temperature of 90° C., and reduced pressure distillation is performed until no liquid is produced to obtain modified polyacrylic acid.

[0098] S2. Preparation of hybrid polyacrylic acid

[0099] Weigh: 15.0g 1,3-diamino-2-hydroxypropane, 5.0g dimethyl carbonate, 1.5g triethylamine and 50.0mL dimethyl sulfoxide, add into the reaction kettle and stir, raise the temperature of the reaction kettle to 70°C, stir at 100rpm, keep warm for 3h, after the reaction is completed, lower the temperature of the reaction kettle to room temperature, place the reaction liquid in a rotary evaporator at 90°C, and distill under reduced pressure until no liquid is produced, to obtain a carbonated cross-linking agent;

[0100] Weigh: 10.0g of carbonated cross-linking agent, 1.6g of triethylamine and 100.0mL of dichloromethane are added to a reactor, the temperature of the reactor is lowered by 3°C, 20.0g of methyl chloroformate is added to the reactor, and the reaction is carried out for 3h at room temperature, and then the temperature of the reactor is raised to 150°C and the reaction is carried out for 5h at room temperature. After the reaction is completed, the reactor is lowered to room temperature, and the reaction liquid is placed in a rotary evaporator at a temperature of 90°C, and the reaction liquid is distilled under reduced pressure until no liquid is produced to obtain a modified cross-linking agent;

[0101] Weigh: 18.0g of polyacrylic acid, 6.0g of modified crosslinking agent and 80.0mL of N,N-dimethylformamide are added to a reactor and stirred. The temperature of the reactor is raised to 70°C, the stirring rate is 100rpm, and the temperature is kept and stirred for 9h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is placed in a rotary evaporator at a temperature of 90°C, and distilled under reduced pressure until no liquid is produced to obtain crosslinked polyacrylic acid;

[0102] Weigh: 20.0 g of cross-linked polyacrylic acid, 6.0 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 1.2 g of triethylamine and 100.0 mL of N,N-dimethylformamide, add into a reactor and stir, raise the temperature of the reactor to 40°C, keep warm and stir for 1 hour, after the reaction is completed, lower the temperature of the reactor to room temperature, place the reaction liquid in a rotary evaporator at a temperature of 90°C, and distill under reduced pressure until no liquid is produced to obtain hybrid polyacrylic acid.

[0103] S3. Preparation of modified filler

[0104] Weigh: 2.0 g of silver nitrate and 50.0 mL of ethanol to obtain a metal alcohol solution;

[0105] Weigh: 0.5 g of graphene and 50.0 mL of ethanol to prepare a graphene dispersion;

[0106] The metal alcohol solution was added dropwise to a reaction kettle containing a graphene dispersion solution and stirred. Ultrasound was performed while stirring at room temperature. The stirring rate was 100 rpm and the ultrasonic frequency was 30 kHz. After the metal alcohol solution was added dropwise, the stirring and ultrasonication were continued for 12 minutes to obtain a reaction solution.

[0107] A 28 wt% ammonia solution was added dropwise to a reaction kettle containing the reaction solution and stirred. The temperature of the reaction kettle was raised to 55°C. The pH of the reaction system was controlled to be 9 while the hydrolyzate was added dropwise. After stirring for 2 hours, the mixture was allowed to stand for 5 hours to obtain a modified gel.

[0108] The modified gel was placed in a vacuum drying oven, the temperature of the vacuum drying oven was increased to 80°C, and after vacuum drying for 11 hours, the material was transferred to a tubular furnace, nitrogen was introduced for protection, the tubular furnace was heated to 360°C at a heating rate of 5°C / min, and the temperature was kept for 3 hours to obtain a modified filler.

[0109] S4. Preparation of conductive adhesive

[0110] Weigh: 12.0 g of hybrid polyacrylic acid, 16.0 g of modified filler, 4.2 g of styrene-butadiene rubber, 2.4 g of polyvinyl pyrrolidone, 2.4 g of polyvinyl pyrrolidone, 1.8 g of sodium dodecylbenzene sulfonate and 72.0 g of deionized water, add into a reaction kettle and stir to obtain a conductive adhesive.

[0111] Comparative Example 1

[0112] The difference between this embodiment and comparative example 3 is that step S1 is eliminated, and in step S2, homopolymerized acrylic acid is used in an equal amount to replace modified polyacrylic acid.

[0113] Comparative Example 2

[0114] The difference between this embodiment and comparative example 3 is that step S1 and step S2 are eliminated, and in step S4, homopolymerized acrylic acid is used to replace hybridized acrylic acid in an equal amount.

[0115] Comparative Example 3

[0116] The difference between this embodiment and comparative example 3 is that step S3 is eliminated, and in step S4, an equal amount of graphene is used to replace the modified filler.

[0117] Performance Testing:

[0118] The volume resistivity, tensile shear strength and thermal conductivity of the conductive adhesives prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard HG / T 5912-2021 "Determination of tensile shear strength of adhesives (rigid material to rigid material)";

[0119] The vertical burning grades of the modified thermally conductive adhesives prepared in Examples 1-3 and Comparative Examples 1-3 were tested with reference to the standard GB / T 2408-2021 “Horizontal and vertical methods for determination of combustion performance of plastics”;

[0120] The limiting oxygen index of the conductive adhesives prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 26526-2011 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test";

[0121] The wear resistance of the conductive adhesives prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard YY / T 0988.15-2016 “Surgical Implant Coatings Part 15: Test Method for Wear Resistance of Metal Thermal Spray Coatings”. The specific data are shown in Table 1.

[0122] Table 1- Performance test data of each test sample

[0123]

[0124]

[0125] Data Analysis:

[0126] By comparing the data in Table 1 above, it can be found that the volume resistivity of the conductive adhesive prepared by the present invention is 654Ω·cm, the tensile shear strength is 11MPa, and the thermal conductivity is 1.6W·(m·K). -1, vertical combustion grade is V-0, limiting oxygen index is 39.2% and mass loss after 100 cycles of wear is only mg;

[0127] Analysis Notes:

[0128] The conductive adhesive prepared by the present invention is mainly composed of hybrid polyacrylic acid, wherein a silane coupling agent is grafted into the hybrid polyacrylic acid, so that the compatibility between the hybrid polyacrylic acid and the inorganic material is greatly improved, and the carbonate component in the crosslinking agent component of the hybrid polyacrylic acid greatly enhances its compatibility with the modified filler and the carbon component in the carbon coating, and a large number of cyanide groups inside the hybrid polyacrylic acid significantly improve the polarity of the modified adhesive, greatly enhancing its adhesion to the metal current collector, and the presence of its epoxy group plays the role of an electrolyte film-forming additive, which is helpful for the formation of the SEI film, and finally significantly improves the shear strength and wear resistance of the material, and in the process of combustion, the carbonate component releases a large amount of carbon dioxide, so that the flame retardant ability of the modified adhesive is significantly improved;

[0129] Silver nitrate is gelled on the graphene surface under alkaline conditions, and after drying and calcining, nanosilver particles form a stable mosaic structure on the graphene surface to obtain a modified filler with strong conductivity. The nanosilver particles and graphene have extremely excellent thermal conductivity, and finally cooperate with hybrid polyacrylic acid to significantly improve the conductive and thermal conductivity of the conductive adhesive.

[0130] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0131] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0132] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A conductive adhesive for carbon coating of a current collector, characterized in that: The invention comprises the following raw materials in weight: 10-12 parts of hybrid polyacrylic acid, 12-16 parts of modified filler, 3-5 parts of styrene-butadiene rubber, 2-3 parts of polyvinyl pyrrolidone, 2-3 parts of polyvinyl pyrrolidone, 1-2 parts of sodium dodecylbenzene sulfonate and 60-80 parts of deionized water; Wherein, the preparation method of hybrid polyacrylic acid comprises the following steps: A1, adding modified polyacrylic acid, modified crosslinking agent and N,N-dimethylformamide into a reaction kettle and stirring, raising the temperature of the reaction kettle to 60-80° C., keeping the temperature and stirring for 8-10 hours, and post-treating to obtain crosslinked polyacrylic acid; A2. Add cross-linked polyacrylic acid, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, triethylamine and N,N-dimethylformamide into a reaction kettle and stir. The temperature of the reaction kettle is increased to 30-50° C. and stirred for 1-2 hours. Post-treatment is performed to obtain hybrid polyacrylic acid.

2. The conductive adhesive for carbon coating of a current collector according to claim 1, characterized in that: In step A1, the stirring rate of the reactor is 80-120 rpm, and the amount ratio of modified polyacrylic acid, modified crosslinking agent and N,N-dimethylformamide is 8-10 g:2-3 g:30-40 mL; in step A2, the amount ratio of crosslinked polyacrylic acid, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, triethylamine and N,N-dimethylformamide is 8-10 g:2-3 g:0.5-0.8 g:40-60 mL.

3. The conductive adhesive for carbon coating of a current collector according to claim 1, characterized in that: The preparation method of the modified polypropylene comprises the following steps: B1. Add 1,4-dichloro-2-butene, sodium cyanide and dimethyl sulfoxide into a reaction kettle and stir. The temperature of the reaction kettle is increased to 100-120° C. and stirred for 4-6 hours. Post-process to obtain a modified monomer. B2. Add modified monomer, acrylic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, azobisisobutylcyanide and dimethyl sulfoxide into a reactor, increase the temperature of the reactor to 80-100°C, keep the reaction warm for 2-4 hours, and obtain modified polyacrylic acid by post-treatment.

4. The conductive adhesive for carbon coating of a current collector according to claim 3, characterized in that: In step B1, the stirring rate of the reactor is 80-120rpm, and the amount ratio of 4-dichloro-2-butene, sodium cyanide and dimethyl sulfoxide is 4-5mL:4-5g:10-15mL; in step B2, the amount ratio of the modified monomer, acrylic acid, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, azobisisobutyronitrile and dimethyl sulfoxide is 3-5g:6-8g:9-12g:0.3-0.5g:60-80mL.

5. The conductive adhesive for carbon coating of a current collector according to claim 1, characterized in that: The preparation method of the modified crosslinking agent comprises the following steps: C1, adding 1,3-diamino-2-hydroxypropane, dimethyl carbonate, triethylamine and dimethyl sulfoxide into a reaction kettle and stirring, raising the temperature of the reaction kettle to 60-80° C., keeping the temperature for reaction for 2-4 hours, and post-treating to obtain a carbonated cross-linking agent; C2. Add the carbonated crosslinking agent, triethylamine and dichloromethane into the reactor, lower the temperature of the reactor by 0-5°C, add methyl chloroformate into the reactor, keep the temperature for 2-4 hours, raise the temperature of the reactor to 100-150°C, keep the temperature for 4-6 hours, and obtain the modified crosslinking agent by post-treatment.

6. The conductive adhesive for carbon coating of a current collector according to claim 5, characterized in that: In step C1, the amount ratio of 1,3-diamino-2-hydroxypropane, dimethyl carbonate, triethylamine and dimethyl sulfoxide is 5-8g:2-3g:0.5-0.8g:20-30mL, and the stirring rate of the reactor is 80-120rpm; in step C2, the amount ratio of the carbonation cross-linking agent, triethylamine, dichloromethane and methyl chloroformate is 3-5g:0.5-0.8g:40-60mL:10-12g.

7. The conductive adhesive for carbon coating of a current collector according to claim 1, characterized in that: The preparation method of the modified filler comprises the following steps: D1. Add the metal alcohol solution dropwise into a reactor containing the graphene dispersion and stir, and perform ultrasonic stirring at room temperature. After the metal alcohol solution is added dropwise, continue stirring and ultrasonic stirring for 10-15 minutes to obtain a reaction solution; D2, adding the hydrolyzate dropwise into the reaction kettle containing the reaction solution and stirring, raising the temperature of the reaction kettle to 50-60°C, controlling the pH of the reaction system to 8-9 while adding the hydrolyzate dropwise, keeping the temperature and stirring for 1-2 hours, and letting it stand for 3-5 hours to obtain a modified gel; D3. Place the modified gel in a vacuum drying oven, raise the temperature of the vacuum drying oven to 80°C, and after vacuum drying for 10-12 hours, transfer the material to a tubular furnace, introduce nitrogen protection, and heat the tubular furnace to 350-400°C at a heating rate of 5°C / min, and keep the temperature for 2-3 hours to obtain a modified filler.

8. The conductive adhesive for carbon coating of a current collector according to claim 1, characterized in that: In step D1, the stirring rate of the reactor is 80-120rpm, the ultrasonic frequency is 20-40kHz, the metal alcohol solution is prepared by silver nitrate and ethanol in a dosage ratio of 1-2g:50mL, the graphene dispersion is prepared by graphene and ethanol in a dosage ratio of 0.2-0.5g:50mL, and the dosage ratio of the metal alcohol solution to the graphene dispersion is 1mL:1-1.5mL; in step D2, the hydrolyzate is a 25-30wt% ammonia solution.

9. A method for preparing a conductive adhesive for carbon coating of a current collector according to any one of claims 1 to 8, characterized in that: Hybrid polyacrylic acid, modified filler, styrene-butadiene rubber, polyvinyl pyrrolidone, sodium dodecylbenzene sulfonate and deionized water are added into a reaction kettle and stirred to obtain a conductive adhesive.

Citation Information

Patent Citations

  • Electroconductive adhesive composition

    CN111918946A